PM10 EMISSION INVENTORY OF INDUSTRIAL AND ROAD TRANSPORT VEHICLES IN KLANG VALLEY, PENINSULAR MALAYSIA - Azman, Azid; Mohd. Asrul, Jamalani; Ahmad Makmom, Abdullah (2018)
Rapid development in industrial and road transportation sector in developing countries has contributing the environmental issue. Determining the estimated PM 10 emission in Klang Valley, Malaysia is based on the best available resources. Emission of PM 10 from both sources was estimated particularly from numbers of industries (industrial area and emission factor) and the usage of motor vehicles (traffic volume, vehicle kilometer travel and emission factor). The PM 10 emission from both industrial and road transportation sector were 88.59 tonne PM 10 /year and 32.36 tonne PM 10 /year respectively. Thus, the total estimated PM 10 emission was 120.95 tonne PM 10 /year. Therefore, the PM 10 emission from both sources in Klang Valley can be estimated based on the best available resources due to limitation of actual PM 10 emission from both sector.